2019
DOI: 10.1002/biof.1517
|View full text |Cite
|
Sign up to set email alerts
|

Novel findings of 18β‐glycyrrhetinic acid on sRAGE secretion through inhibition of transient receptor potential canonical channels in high‐glucose environment

Abstract: Enhancing soluble receptor for advanced glycation endproducts (sRAGE) is considered as a potent strategy for diabetes therapy. sRAGE secretion is regulated by calcium and transient receptor potential canonical (TRPC) channels. However, the role of TRPC channels in diabetes remains unknown. 18β‐Glycyrrhetinic acid (18β‐GA), produced from liquorice, has shown antidiabetic properties. This study was aimed to investigate the effect of 18β‐GA on sRAGE secretion via TRPC channels in high glucose (HG)‐induced THP‐1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The GLAST in Müller cells is mainly responsible for maintaining low synaptic glutamate levels in the retina. Significant decreases in glutamate transport mediated via the GLAST in Müller cells begins after just 4 weeks in diabetic rat models (Puro, 2002), which is consistent with reports showing significantly increased glutamate accumulation in diabetic rat retinas (Lieth et al, 1998;Lieth et al, 2000). Although the mechanism of dysfunction of the GLAST in Müller cells under HG remains unknown, Li et al suggested that the dysfunction of GLAST is mainly caused by increased ROS levels (Li and Puro, 2002).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The GLAST in Müller cells is mainly responsible for maintaining low synaptic glutamate levels in the retina. Significant decreases in glutamate transport mediated via the GLAST in Müller cells begins after just 4 weeks in diabetic rat models (Puro, 2002), which is consistent with reports showing significantly increased glutamate accumulation in diabetic rat retinas (Lieth et al, 1998;Lieth et al, 2000). Although the mechanism of dysfunction of the GLAST in Müller cells under HG remains unknown, Li et al suggested that the dysfunction of GLAST is mainly caused by increased ROS levels (Li and Puro, 2002).…”
Section: Discussionsupporting
confidence: 71%
“…Hyperglycemia is a major risk factor for various human diseases. Multiple studies have reported that the excitotoxicity caused by elevated glutamate in the extracellular space in experimental models of diabetes plays an important role in the pathophysiology of DR (Lieth et al, 1998;Lieth et al, 2000;Kowluru et al, 2001). Our results indicate Müller cells treated with 25 mM glucose exhibit decreased glutamate uptake activity because of decreased expression of the GLAST.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Su et al (3) indicated that 18β-GA lessened the severity of radiation-induced skin injury and decreased inflammatory infiltration and the levels of TNF-α, IL-1β and IL-6 in dermal tissues by decreasing NADPH oxidase activity and reactive oxygen species (ROS) production and suppressing the activation of p38 MAPK and NF-κB signalling. 18β-GA demonstrated considerable functions similar to those of Pyr3 or 2-aminoethyl diphenylborinate inhibitors and suppressed high glucose-induced effects, including the blockade of transient receptor potential (TRP) cation channel subfamily C member 3 (TRPC3) and TRPC6 protein expression and decreases in ROS and inducible nitric oxide synthase expression (16). Based on the determinant role of 18β-GA in inhibiting ROS generation and inflammatory infiltration, it was hypothesized that 18β-GA protects against nerve injury caused by hydrogen peroxide (H 2 O 2 ).…”
Section: Protective Effect Of 18β-glycyrrhetinic Acid Against H 2 O 2 -Induced Injury In Schwann Cells Based On Network Pharmacology and mentioning
confidence: 99%
“…GA is reported to demonstrated a wide range of significant biological effects viz., anti-inflammatory [34,35], hepatoprotective [36,37], antiviral [38,39], cytotoxic effects [40,41]. In addition, GA is reported to treat liver diseases [42] and diabetes [43]. Moreover, GA synthetic derivatives exhibited anti-inflammatory effects [44], anti-HCV effects [45], and antimicrobial effects [46].…”
Section: Introductionmentioning
confidence: 99%